Moradia estudantil como lugar de convivência em Manaus - AM - Moreira, Mariane Soares (Brasil, 2022)
This work proposes the project of a student housing with space for coexistence, destined to shelter University students with socioeconomic vulnerability coming from other cities to study in Manaus. The proposed building aims to offer a place that serves students in order to improve their quality of life and encourage good coexistence with everyone, through appropriate solutions for a public building, with low maintenance costs and high durability. The work is contextualized through bibliographical research around student housing, study and diagnosis of the intervention area and analysis of design references relevant to the topic. Based on this, we present guidelines for designing the project, as well as sketches and schemes inherent to the development of the housing proposal. Keywords: Student housing, public housing, social vulnerability, living space.